21st century nanoscience -- a handbook : Low-dimensional materials and morphologies. (Volume Four) - Sattler, Klaus D. ([Place of publication not identified] : CRC Press, 2020)
21st Century Nanoscience - A Handbook: Low-Dimensional Materials and Morphologies (Volume 4)will be the most comprehensive, up-to-date large reference work for the field of nanoscience. Handbook of Nanophysics by the same editor published in the fall of 2010 and was embraced as the first comprehensive reference to consider both fundamental and applied aspects of nanophysics. This follow-up project has been conceived as a necessary expansion and full update that considers the significant advances made in the field since 2010. It goes well beyond the physics as warranted by recent developments in the field. This fourth volume in a ten-volume set covers low-dimensional materials and morphologies. Key Features: Provides the most comprehensive, up-to-date large reference work for the field. Chapters written by international experts in the field. Emphasises presentation and real results and applications. This handbook distinguishes itself from other works by its breadth of coverage, readability and timely topics. The intended readership is very broad, from students and instructors to engineers, physicists, chemists, biologists, biomedical researchers, industry professionals, governmental scientists, and others whose work is impacted by nanotechnology. It will be an indispensable resource in academic, government, and industry libraries worldwide. The fields impacted by nanophysics extend from materials science and engineering to biotechnology, biomedical engineering, medicine, electrical engineering, pharmaceutical science, computer technology, aerospace engineering, mechanical engineering, food science, and beyond.
Advances in 1D Materials - Palomino GarateSurvey of Low-Dimensional Materials -JiangLow-Dimensional Hybrid Nanomaterials -AhmadAromatic Helicenes -StaraSupported Two-Dimensional Metal Clusters -Guo, Q.A Novel Class of Two-Dimensional Materials: Transition Metal Dichalcogenides - ZhaoTwo-Dimensional Gallium Nitride - BehzadGraphene Nanodot Arrays -CamilliGraphene Nanomeshes -MaaroufDielectric Harmonic Nanoparticles: Optical Properties, Synthesis, and Applications -BonacinaFundamentals of Laser-Generated Nanoparticles in Liquid Phase -OrtacNanoparticles at the Polarized Liquid-Liquid Interface - OpalloTerahertz Resonance of Nanoparticles in Water - GordonWater Photosplitting on Gold Nanoparticles: Quantum Selectivity and Dynamics - MengOnion-Like Inorganic Fullerenes from a Polyhedral Perspective - ChangMagnetic Properties of Endohedral Fullerenes: Applications and Perspectives - PorfyrakisTitania Nanotubes - VargheseCarbon Nanotubes and Carbon Nanotube Fibers - AbotHall Effect Characterization of Nanowires - HultinMetal Oxide Nanowire Arrays - GuitonElectrospinning and Electrospun Nanofibers - ZhangNanopore Structures and their Applications - WangMethane Storage in Nanoporous Carbons - CabriaMetal Hydroxide and Oxide Nanocages -Guo, L.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Nanotechnology; SCIENCE / Solid State Physics; TECHNOLOGY / Material Science; Nanoscience -- Handbooks, manuals, etc